PENGARUH BAGI HASIL,KUALITAS PELAYANAN DAN KELUARGA TERHADAP KEPUTUSAN MENJADI NASABAH BANK MUAMALAT (STUDI KASUS DI KABUPATEN LAMONGAN) - fathur rohman wahid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to examine the effect of the principle of profit sharing, service quality, and family on the decision to become a customer at bank muamalat. The population in this study were all customers of the Muamalat branch office (KCP) Lamongan Regency, totaling 1834 with a total sample of 120 customers. The sample selection was carried out using the Hair et al (1998) formula in which the number of indicators was multiplied by 6 sampling methods using probability sampling. The analytical method used is multiple linear regression. The results showed that the principle of profit sharing, service quality, family had a significant effect on the decision to become a customer at bank muamalat, which had an Fcount of 59.886 > 2.68 and had a significant value of 0.000 <0.05.